2021
DOI: 10.1029/2021gl094494
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Pulsating Aurora and Microburst Observations With Ground‐Based Fast Auroral Imagers and CubeSat FIREBIRD‐II

Abstract: A pulsating aurora is a type of diffuse aurora usually occurring on the morning side (Akasofu, 1968) and characterized by brightness modulation in both space and time. The modulating period of the pulsating aurora has a hierarchical structure. A few to a few-tens of second modulation is called the main pulsation, and a ∼3-Hz modulation embedded within the main pulsation is called the internal modulation. The pulsating aurora is produced by the precipitation of magnetospheric electrons with energies ranging fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…The latitudinal propagating chorus waves cause wide energy electron precipitations from keV energy (pulsating aurora) and MeV energy (relativistic electron microbursts) because the resonance energy depends on the magnetic latitudes. This model is consistent with recent studies that use conjugate observations between ground-based observations and SAMPEX and FIREBIRD (Kawamura et al, 2021;Shumko et al, 2021;Zhang et al, 2022).…”
supporting
confidence: 92%
“…The latitudinal propagating chorus waves cause wide energy electron precipitations from keV energy (pulsating aurora) and MeV energy (relativistic electron microbursts) because the resonance energy depends on the magnetic latitudes. This model is consistent with recent studies that use conjugate observations between ground-based observations and SAMPEX and FIREBIRD (Kawamura et al, 2021;Shumko et al, 2021;Zhang et al, 2022).…”
supporting
confidence: 92%
“…They have shown that electrons with wide energy range of tens to hundreds of keV precipitate, in association with pulsating auroras, as a result of the interaction of the electrons with whistler mode chorus waves propagating from the equator along the geomagnetic field lines. Miyoshi et al (2020) have proposed a model that the relativistic electron microburst is a high-energy tail of the pulsating aurora, which was later confirmed by recent observational studies (Kawamura et al, 2021;Miyoshi et al, 2021;Shumko et al, 2021).…”
mentioning
confidence: 81%
“…Examples include studies linking FIREBIRD-II observed precipitation to waves in the source region (Breneman et al, 2017;Capannolo et al, 2019aCapannolo et al, , 2019bChen et al, 2020;Colpitts et al, 2020) and to the pulsating aurora, a ground-based diagnostic of electron precipitation (Kawamura et al, 2021). We note that plans were made to compare FIREBIRD-II observations with another potential contemporary set of measurements made by a similar instrument (Kanekal et al, 2019), however the NASA CeReS CubeSat mission ended prematurely only 5 days after launch in late December 2018.…”
Section: Firebird-ii Science Achievementsmentioning
confidence: 96%
“…However, FIREBIRD is answering this final highest-level objective and other science questions in combination with other contemporary space and ground assets such as the BARREL balloon mission (Millan et al, 2013), the NASA Van Allen Probes mission, the Japanese Arase mission, ground radar and imaging facilities, and CSSWE. Examples include studies linking FIREBIRD-II observed precipitation to waves in the source region (Breneman et al, 2017;Capannolo et al, 2019aCapannolo et al, , 2019bChen et al, 2020;Colpitts et al, 2020) and to the pulsating aurora, a ground-based diagnostic of electron precipitation (Kawamura et al, 2021). We note that plans were made to compare FIREBIRD-II observations with another potential contemporary set of measurements made by a similar instrument (Kanekal et al, 2019), however the NASA CeReS CubeSat mission ended prematurely only five days after launch in late Decemeber 2018.…”
Section: Firebird-ii Science Achievementsmentioning
confidence: 98%